Performance analysis & energy benefits of a desiccant based solar assisted trigeneration system in a building. (January 2016) - Hands, Stuart; Sethuvenkatraman, Subbu; Peristy, Mark; Rowe, Daniel; White, Stephen
Abstract: In this paper, performance details and operational benefits of a large scale solar trigeneration system that provides for solar assisted desiccant cooling, heating and hot water generation installed in a teaching institute building have been reported. A two-rotor desiccant system designed for handling 12 000 m3/hr of air was integrated into existing plant to provide a net reduction in energy consumption over the pre-existing heating ventilation and air-conditioning and domestic hot water systems. The system is controlled and monitored by a building management system which has been used to investigate and analyse the typical system behaviour. Heat from solar energy contributed consistently to reduce gas usage for water heating and on an annual basis showed a reduction of 21% of consumed energy. The solar energy contribution for space heating varied over winter months and during some months it was observed to contribute more than 50% of the total energy requirements for space heating. Under suitable ambient conditions, approximately 35% of total building cooling load was met by the solar driven desiccant cooling system. Continuous monitoring has also helped understand some of the operational issues of the system. Highlights: Solar assisted cooling, heating and domestic hot water system with thermal storage system designed and commissioned. Two wheel solid desiccant system for reducing building cooling load requirements. The system has been monitored continuously, this paper reports one year operational data covering one annual weather cycle. Performance of the system analysed to identify potential design & operational issues. Energy benefits of the system calculated.